Creating electronic access to newspaper information in Nigeria: the information aid network (IFAnet) experience (2006)
This paper highlights the value of newspaper information and the methods adopted in organizing, preserving and disseminating it. The paper dwells on the traditional ways of managing newspaper resources and the need to device a new medium of accessing the information contents of the resource. It enumerates the steps taken in conserving newspaper information and building access descriptors for retrieval from the massive information contained in numerous newspapers churned out daily, weekly or periodically. An NGO, (IFAnet), concerned with managing information and using newspapers as one of its major resources has been used as the case study